2019
DOI: 10.1093/mnras/stz2187
|View full text |Cite
|
Sign up to set email alerts
|

Probing inhomogeneity in the helium ionizing UV background

Abstract: We present an analysis combining the simultaneous measurement of intergalactic absorption by hydrogen (H i), helium (He ii) and oxygen (O vi) in UV and optical quasar spectra. The combination of the H i and He ii Lyman-alpha forests through η (the ratio of column densities of singly ionized helium to neutral hydrogen) is thought to be sensitive to large-scale inhomogeneities in the extragalactic UV background. We test this assertion by measuring associated five-times-ionized oxygen (O vi) absorption, which is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…These measurements are in agreement with the predictions based on the stochasticity of the space density of ionizing sources such as high-z AGNs and the partial reionization of optically thick absorbers near the completion of the reionization process (Compostella et al 2014;Chardin et al 2015Chardin et al , 2017Madau 2017). In practice, strong fluctuations in HeII absorption could be due to spatial variation of the hard UV background in an already ionized medium at z ∼ 3 (Morrison et al 2019). A soft UV background produced by a homogeneous distribution of ubiquitous ultra-faint SFGs at z > 10 is in tension with such measurements.…”
Section: The Igm Temperature and The Heii Reionization In An Agn-driv...supporting
confidence: 88%
“…These measurements are in agreement with the predictions based on the stochasticity of the space density of ionizing sources such as high-z AGNs and the partial reionization of optically thick absorbers near the completion of the reionization process (Compostella et al 2014;Chardin et al 2015Chardin et al , 2017Madau 2017). In practice, strong fluctuations in HeII absorption could be due to spatial variation of the hard UV background in an already ionized medium at z ∼ 3 (Morrison et al 2019). A soft UV background produced by a homogeneous distribution of ubiquitous ultra-faint SFGs at z > 10 is in tension with such measurements.…”
Section: The Igm Temperature and The Heii Reionization In An Agn-driv...supporting
confidence: 88%
“…(vii) The results support the findings of Morrison et al (2019) that O shows inhomogeneity on scales of several 10s of comoving megaparsecs, reaching even 100 cMpc h −1 . This work goes a step further, however, confirming expected connection to the quasar population.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand three of our > 3 detections are not marginal and our O results are particularly robust. The overall the picture presented in Morrison et al (2019) of inhomogeneities in the O on several 10s of cMpc is strongly supported here, despite the very different data and analysis methods used. Indeed, we are able to go further than that work and confirm that these inhomogeneities are at least correlated with quasar positions.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Theoretical models have often assumed the UVB is spatially homogeneous and externally imposed (e.g., Oppenheimer et al 2010;van de Voort et al 2011;Keating et al 2016;Rahmati et al 2016), but such models have often been unsuccessful in reproducing observed properties of C iv absorbers at z ≥ 4 (Oppenheimer et al 2009;Rahmati et al 2016;Finlator et al 2016;Finlator et al 2018). High redshift observational studies have also identified a need for variations in the local ionizing radiation field around absorbers (e.g., D 'Odorico et al 2013;Boksenberg & Sargent 2015;Morrison et al 2019).…”
Section: Physical Interpretationsmentioning
confidence: 99%